Ion Solvation and the Search for a Correlation with Electrode Passivation. Issue 1740 (13th May 2015) - von Wald Cresce, Arthur; Russell, Selena M.; Fu, Adele; Wikner, Emily; Xu, Kang; Gobet, Mallory; Greenbaum, Steven
ABSTRACT: The solvation of cations and anions in a lithium-containing electrolyte was studied using electrospray ionization mass spectrometry (ESI-MS) combined with nuclear magnetic resonance (NMR) and electrochemical testing. The purpose of these experiments was to develop an understanding of the solvation of the small, hard Li + cation and the more cryptic nature of the solvation of poorly-coordinating anions such as PF6 - and BF4 - . It has long been held that the passivation of graphitic anodes in lithium ion batteries is a solvation-driven process, meaning that whatever solvent molecules surround the Li + cation will provide the raw material for the formation of the solid electrolyte interphase (SEI) layer. Because the SEI is a critical component, and because a binary solvent system is normally used in lithium batteries, it is necessary to understand the competitive nature of lithium solvation. Conversely, the anion can be chemically active even if poorly coordinating; therefore, it was desired to see if a competitive solvation condition exists for the anion as well. Results indicate that Li + has a strong preference for cyclic carbonates like ethylene carbonate (EC) over linear carbonates, where the anions had a mixed preference. It is thought that anion solvent preference might dictate oxidative chemistry that occurs on the cathode, while the anion also significantly participates in the formation of SEI on the anode.